PERANCANGAN EVENT TRADING CARD GAME SEBAGAI BRAND ACTIVATION UNTUK MEMPERKENALKAN PRODUK CARD GAME HEXAGA - Budijono, Dwi Susestiyo; Budi, Hutomo Setia (Jurnal VICIDI, 2020)
This design is made in order to make a trading card game event to introduce the card game hexaga in Surabaya. To introduce the event to Surabaya people, Hexaga game card will held a small event to introduce the card game Hexaga to a small card community. The event aims to make some of the players know the game and introduced the card game Hexaga to other players directly or indirectly. The main goal hexaga strengthen community card game that had the old players who know the game before the main event.